Equivalent Property of a Hilbert-Type Integral Inequality Related to the Beta Function in the Whole Plane - Dongmei Xin; Bicheng Yang; Aizhen Wang (Journal of Function Spaces)
By means of the technique of real analysis and the weight functions, a few equivalent statements of a Hilbert-type integral inequality with the nonhomogeneous kernel in the whole plane are obtained. The constant factor related to the beta function is proved to be the best possible. As applications, the case of the homogeneous kernel, the operator expressions, and a few corollaries are considered.